Vulvodynia: What is available online? A systematic review of information on the internet. Issue 8 (14th June 2022) - Loganathan, Jemina; Ghai, Vishalli; Ilaalagan, Ragave; Doumouchtsis, Stergios K.; ,
Abstract: Aim: This review aimed to evaluate the quality of medicalinformation online for patients relating to vulvodynia. To our knowledge no evaluation of online patient information exists regarding vulvodynia and, at present, there is no standardized or validated method of evaluating medical information on the internet. Methods: A clearly defined protocol was developed to generate keywords relating to vulvodynia. The three most popular search engines worldwide; google.com, yahoo.com, and bing.com, were searched in September 2020. Three assessors evaluated eligible webpages for accuracy, credibility, readability, and reliability. Results: Forty‐five webpages were eligible with 38% given HON certification or Information Standard approval. Only one webpage achieved a DISCERN score of ≥63 indicating excellent reliability. No webpages scored a maximum 10 points for credibility. Eleven percent of webpages were rated "accurate" with score 17 or above. The modal Flesch Kincaid Grade Level was 9 with only 15.6% having a readability grade level of 8 or less. Conclusions: It has been shown in previous studies that patient information available online pertaining to gynecological conditions is frequently inaccurate, with limited regulation and low reliability, and our findings are in agreement with this. As patients increasingly look to the internet for medical information and education, we as clinicians, need to ensure the resources available are of a high standard and regulated. Without ensuring safe and effective healthcare resources, we risk misinformation which can negatively impact clinical care.